Resin film for package
By using polyester fiber (PET) and atmosphere barrier layer in the packaging material, and adjusting the surface chemical structure of the PET film through TOF-SIMS analysis, the problem of airtightness failure of the packaging material under the action of external forces is solved, and higher resistance to deformation and airtightness is achieved.
Patent Information
- Application Number
- JP2024231601
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2041-03-17
AI Technical Summary
The airtightness of existing packaging materials is prone to failure under external forces, resulting in the packaging being no longer sealed.
A composite packaging material containing polyester fiber (PET) and atmosphere barrier layer is used, where the PET film is adjusted by TOF-SIMS analysis to improve airtightness.
By adjusting the surface chemical structure of the PET film, the deformation resistance and airtightness of the packaging material are enhanced, ensuring that the packaging can still maintain the sealing effect under the action of external forces.
Smart Images

Figure 2025039607000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin film for packaging. [Background technology]
[0002] Resin films containing polyethylene terephthalate are widely used as packaging materials for packaging objects such as food, medicines, and cosmetics. In order to prevent deterioration in the quality of the objects, it is preferable that the packaging material has gas barrier properties that make it difficult for gases such as oxygen and water vapor to pass through. For this reason, a laminate of a transparent film and a barrier layer containing a metal film or a metal oxide film is used as the packaging material (see, for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-81607 A Summary of the Invention [Problem to be solved by the invention]
[0004] On the other hand, during the distribution process of a product whose contents are packaged in a package made of a laminate of a resin film and a gas barrier layer, external forces that cause deformation such as friction and bending are repeatedly applied to the product. When external forces are repeatedly applied to the package in this way, cracks are formed in the gas barrier layer, and the airtightness of the package is lost. Therefore, the laminate is required to comprehensively improve the airtightness of the package by not only improving the gas barrier property but also increasing the resistance to deformation. [Means for solving the problem]
[0005] The laminate for packaging to solve the above problems includes a resin film and a gas barrier layer. The resin film contains polyethylene terephthalate, and when analyzed using time-of-flight secondary ion mass spectrometry (TOF-SIMS), it is found to have a gas barrier property of C7H4O + The peak intensity of (m / z=104) is C3H5 + The standard value divided by the peak intensity of (m / z=41) is within the range of 0.1 to 0.5. The packaging body for solving the above problem includes the above resin film for packaging body and a gas barrier layer. The resin film for packaging to solve the above problems is a resin film for packaging provided in a laminate for packaging comprising a resin film and a gas barrier layer. The resin film for packaging contains polyethylene terephthalate, and when analyzed using time-of-flight secondary ion mass spectrometry (TOF-SIMS), it is found to be C7H4O + The peak intensity of (m / z=104) is C3H5 + The standard value divided by the peak intensity of (m / z=41) is within the range of 0.1 to 0.5.
[0006] The present inventors have conducted extensive research into a resin film for packaging that can suppress a decrease in gas barrier properties when an external force is applied when the resin film for packaging is applied to a laminate for packaging, and have found the following. + The peak intensity of (m / z=104) is C3H5 + The inventors of the present application have discovered that when the standard value divided by the peak intensity of (m / z=41) is within the range of 0.1 or more and 0.3 or less, the airtightness of a package including the resin film is improved.
[0007] In this regard, according to the above-mentioned resin film for packaging, laminate for packaging, and packaging body, the standard value is within the range of 0.1 or more and 0.5 or less, so it is possible to improve the airtightness of the packaging body.
[0008] In the laminate for packaging, the gas barrier layer may include a vapor deposition layer and a coating film, and the vapor deposition layer may be formed of at least one of aluminum oxide and silicon oxide.
[0009] In the laminate for packaging, the vapor deposition layer and the coating film may be in contact with each other. In the laminate for packaging, the coating film is Si(OR 1 )4, or R 2 Si(OR 3 )3(OR 1 and OR 3 is a hydrolyzable group, R 2 is an organic functional group) or one or more hydrolyzates of a silicon compound, and a water-soluble polymer having a hydroxyl group. Effect of the Invention
[0010] According to the present invention, the airtightness of the package can be improved comprehensively. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a cross-sectional view showing a structure of a resin film according to one embodiment. [Diagram 2] FIG. 2 is a cross-sectional view showing a structure of a laminate according to one embodiment. [Diagram 3] FIG. 2 is a perspective view showing a structure of a packaging body in one embodiment. [Figure 4] 13 is a spectrum obtained by TOF-SIMS for the resin film of Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] An embodiment of a laminate for a packaging body, a packaging body, and a resin film for a packaging body will be described with reference to Fig. 1 to Fig. 4. Below, the resin film for a packaging body, the laminate for a packaging body, the packaging body, and examples will be described in this order.
[0013] [Packaging resin film] The resin film for packaging (hereinafter, resin film) will be described with reference to FIG. The resin film 10 shown in FIG. 1 contains polyethylene terephthalate (PET). When the resin film 10 was analyzed using time-of-flight secondary ion mass spectrometry (TOF-SIMS), the following was found: C7H4O + The peak intensity of (m / z=104) is C3H5 + The standard value divided by the peak intensity of (m / z=41) is within the range of 0.1 to 0.5.
[0014] C7H4O + is expressed by the following equation (1).
[0015] [ka]
[0016] C7H4O + is derived from a dicarboxylic acid unit among the repeating units contained in the PET forming the resin film 10. + are secondary ions generated from dicarboxylic acid units on the surface of the resin film 10 by irradiating the surface of the resin film 10 with an ion beam, which is a primary ion. The dicarboxylic acid units are composed of a repeating unit derived from terephthalic acid (terephthalic acid unit) represented by the following formula (2) and a repeating unit derived from isophthalic acid (isophthalic acid unit) represented by the following formula (3).
[0017] [ka]
[0018] [ka]
[0019] Also, C3H5 +The peak of C3H5 has an appropriate intensity when the surface of the resin film 10 is analyzed by TOF-SIMS. + Peak of C7H4O + This is used as a criterion for evaluating the intensity of the peak.
[0020] The PET forming the resin film 10 includes at least one of virgin PET and recycled PET. Virgin PET is PET newly synthesized from raw materials such as petroleum. Recycled PET is regenerated PET. Recycled PET may be at least one of PET regenerated by mechanical recycling and PET regenerated by chemical recycling.
[0021] In mechanical recycling, PET products are crushed and the crushed pieces are washed to remove surface dirt and foreign matter, and the resin is then exposed to high temperatures to remove any contaminants trapped inside the resin. In chemical recycling, PET products are crushed and the crushed pieces are washed to remove surface dirt and foreign matter, then the resin is depolymerized back to its intermediate raw material, which is then purified and repolymerized.
[0022] Mechanical recycling does not require large-scale facilities for chemical reactions, and therefore the costs and environmental impacts required for producing recycled PET are lower than those of chemical recycling. Therefore, from the viewpoint of reducing the costs and environmental impacts of producing the resin film 10, the recycled PET contained in the resin film 10 is preferably PET regenerated by mechanical recycling.
[0023] When the resin film 10 contains both recycled PET and virgin PET, the proportion of recycled PET is preferably within the range of 60% by weight to 100% by weight in terms of reducing the cost and environmental impact of producing the resin film 10. The PET product to be recycled may be, for example, a used PET bottle.
[0024] The repeating units of PET include the above-mentioned dicarboxylic acid units and diol units. In virgin PET, an example of the diol unit is a repeating unit derived from ethylene glycol, and an example of the dicarboxylic acid unit is a repeating unit derived from terephthalic acid.
[0025] In recycled PET, an example of the diol unit is a repeating unit derived from ethylene glycol, and an example of the dicarboxylic acid unit includes a repeating unit derived from terephthalic acid and a repeating unit derived from isophthalic acid. In the PET forming the above-mentioned PET bottle, the dicarboxylic acid unit includes a repeating unit derived from terephthalic acid and a repeating unit derived from isophthalic acid, in order to suppress crystallization of the PET and improve the workability of the material. Therefore, the dicarboxylic acid unit of recycled PET made from PET bottles includes terephthalic acid and isophthalic acid, which are the dicarboxylic acid units of PET bottles.
[0026] When the resin film 10 contains both virgin PET and recycled PET, the proportion of repeating units derived from isophthalic acid in all dicarboxylic acid units in the resin film 10 may be, for example, 0.5 mol % or more and 5 mol % or less.
[0027] The virgin PET may be a resin obtained by blending the first resin and the second resin. In this case, the first resin may be a resin obtained by copolymerizing terephthalic acid, isophthalic acid, and naphthalenedicarboxylic acid, or a resin obtained by copolymerizing terephthalic acid and isophthalic acid. The second resin may be a polyethylene naphthalate resin. This allows the virgin PET to contain, as dicarboxylic acid units, repeating units derived from terephthalic acid and repeating units derived from isophthalic acid.
[0028] Furthermore, the virgin PET may be a copolymer polyester mainly composed of ethylene terephthalate units and containing other polyester units. In this case, the copolymer polyester may contain isophthalic acid and naphthalene dicarboxylic acid. This allows the virgin PET to contain, as dicarboxylic acid units, repeating units derived from terephthalic acid and repeating units derived from isophthalic acid. Furthermore, in the copolymer polyester, the dicarboxylic acid units may be repeating units derived from adipic acid. Furthermore, the diol units may be repeating units derived from propylene glycol, 1,4-butanediol, tetramethylene glycol, neopentyl glycol, cyclohexanedimethanol, diethylene glycol, and the like.
[0029] The naphthalenedicarboxylic acid may be at least one of 2,6-naphthalenedicarboxylic acid, 2,7-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, and 1,5-naphthalenedicarboxylic acid. The repeating unit derived from naphthalenedicarboxylic acid is a naphthalenedicarboxylic acid unit.
[0030] The resin film for packaging according to the present disclosure is + The peak intensity of (m / z=104) is C3H5 + The specification value divided by the peak intensity of (m / z=41) is within the range of 0.1 to 0.5. TOF-SIMS irradiates a sample surface with primary ions and measures the mass of secondary ions emitted from the surface, and can measure secondary ions generated from the very vicinity of the sample surface, but the secondary ion generation mechanism in TOF-SIMS is extremely complex. The inventors presume that the following two factors contribute greatly to setting the specification value within the range.
[0031] (Factor 1) Amount of isophthalic acid contained in the resin film By adjusting the isophthalic acid units, the resin film has flexibility suitable for use in packaging materials. Even if external forces such as friction, piercing, bending, or impact are applied to the packaging material, the resin film can absorb the load by deforming in response to the external force, making it difficult for pinholes or tears to form in the adjacent gas barrier layer.
[0032] (Factor 2) Naphthalenedicarboxylic acid contained in the resin film By adjusting the naphthalenedicarboxylic acid unit, the plane orientation coefficient of the resin film can be increased. The plane orientation coefficient is considered to contribute to the secondary ion generation mechanism. By increasing the plane orientation coefficient, the gas barrier property of the resin film itself is improved. Therefore, the airtightness of the package having the gas barrier layer laminated thereon can be comprehensively improved.
[0033] In the resin film of the present disclosure, the molar ratio of isophthalic acid units to the total amount of dicarboxylic acid units and diol units is 2×10 -1 mol% or more 9×10 -1 1.0 mol% or less, and the molar ratio of naphthalenedicarboxylic acid units is 1×10 -2 mol% or more 6×10 -2 Because it is less than mol%, C7H4O + The peak intensity of (m / z=104) is C3H5 + The standard value divided by the peak intensity of (m / z=41) can be within the range of 0.1 to 0.5.
[0034] The average molecular weight of the PET is preferably, for example, from 1000 to 1 million. The resin film 10 may contain various additives. The additives may be, for example, plasticizers.
[0035] The resin film 10 is formed of a single layer or multiple layers. When the resin film 10 is formed of multiple layers, the materials forming each layer may be the same or different from each other. An example of the resin film 10 in which the layers are formed of different materials is a laminate of a layer formed of recycled PET and a layer formed of virgin PET. Another example of the resin film 10 in which the layers are formed of different materials is a laminate of a layer containing recycled PET at a first ratio to virgin PET and a layer containing recycled PET at a second ratio to virgin PET that is different from the first ratio.
[0036] The thickness of the resin film 10 is selected according to various properties required for the package. The properties required for the package may be, for example, various environmental resistances such as heat and moisture, storage stability of the contents, filling property of the contents, sealing processability, and printing resistance including marking. From the viewpoint of improving the processability of the resin film 10, for example, the thickness of the resin film 10 is preferably within a range of 3 μm or more and 100 μm or less, and more preferably within a range of 6 μm or more and 50 μm or less.
[0037] The method for forming the resin film 10 may be, for example, a melt extrusion method or a melt coextrusion method. The resin film 10 may be cooled by a cooling roll, air, water, or the like. The flow direction of the resin film 10 is the direction in which the molding of PET progresses during the production of the resin film 10. The flow direction is also called the MD (Machine Direction) direction or the longitudinal direction. The direction perpendicular to the flow direction is also called the TD (Transverse Direction) direction or the lateral direction. When the resin film 10 is composed of multiple layers, the flow direction of each layer is the same.
[0038] The resin film 10 is a non-stretched film, a uniaxially stretched film stretched at a predetermined ratio in the MD or TD, or a biaxially stretched film stretched at a predetermined ratio in the MD and TD sequentially or simultaneously. When the resin film 10 is composed of multiple layers, the stretching direction of each layer is the same.
[0039] [Laminated body for packaging] The laminate for packaging (hereinafter, laminate) will be described with reference to FIG. 2, the laminate 20 includes a resin film 10 and a gas barrier layer 11. The gas barrier layer 11 has a function of enhancing the gas barrier properties of the laminate 20.
[0040] The gas barrier layer 11 includes, for example, a vapor-deposited film. The vapor-deposited film is an inorganic oxide film or a metal film. The inorganic substance included in the inorganic oxide may be, for example, an oxide of silicon, aluminum, magnesium, calcium, potassium, tin, sodium, boron, titanium, lead, zirconium, yttrium, or the like. The metal may be, for example, aluminum, magnesium, tin, sodium, titanium, lead, zirconium, yttrium, gold, chromium, or the like.
[0041] The method for forming the vapor-phase deposition film may be, for example, a vacuum deposition method, a sputtering method, an ion plating method, or a plasma vapor deposition method (CVD). From the viewpoint of increasing the productivity of the laminate, the method for forming the vapor-phase deposition film is preferably a vacuum deposition method. In the vacuum deposition method, it is preferable to use any one of an electron beam heating method, a resistance heating method, and an induction heating method as a method for heating the deposition material. From the viewpoint of increasing the degree of freedom in the selection of the deposition material, it is preferable to use an electron beam heating method. From the viewpoint of increasing the adhesion between the vapor-phase deposition film and the resin film 10 and from the viewpoint of increasing the density of the vapor-phase deposition film, it is possible to use a plasma assist method and an ion beam assist method in the vacuum deposition method. From the viewpoint of increasing the transparency of the deposition layer, the gas barrier layer 11 may be formed by a reactive deposition method. In the reactive deposition method, a reactive gas such as oxygen gas is supplied to the film formation space.
[0042] The laminate 20 for forming a transparent packaging body comprises a vapor-phase deposited film formed from an inorganic oxide. The inorganic oxide is preferably aluminum oxide or silicon oxide. The laminate 20 for forming a light-shielding packaging bag comprises a vapor-phase deposited film formed from a metal. The metal is preferably aluminum.
[0043] The gas barrier layer 11 may be formed of a plurality of barrier layers. In this case, each barrier layer may be formed of the same material, or the plurality of barrier layers may include a barrier layer formed of a first material and a barrier layer formed of a second material different from the first material.
[0044] The thickness of the gas barrier layer 11 is, for example, within a range of 5 nm to 300 nm. When the thickness of the gas barrier layer 11 is 5 nm or more, the uniformity of the gas barrier layer 11 can be increased and the gas barrier layer 11 can have a sufficient thickness. Therefore, the gas barrier layer 11 can fully exhibit the gas barrier function. On the other hand, when the thickness of the gas barrier layer 11 is 300 nm or less, the gas barrier layer 11 can maintain flexibility. This suppresses cracks in the gas barrier layer 11 caused by external factors. The external factors include, for example, bending and pulling the laminate 20 after the gas barrier layer 11 is formed. The thickness of the gas barrier layer 11 is appropriately selected depending on the type of inorganic compound forming the gas barrier layer 11 and the layer structure of the laminate 20. From the viewpoint of increasing the uniformity in the thickness of the gas barrier layer 11, it is more preferable that the thickness of the gas barrier layer 11 is within a range of 10 nm to 150 nm.
[0045] The gas barrier layer 11 may include a coating film having gas barrier properties in addition to or instead of the above-mentioned vapor-phase deposition film. The coating film is formed of a material containing a resin. In the following, an example will be described in which the gas barrier layer 11 includes a coating film formed on a vapor-phase deposition film of an inorganic oxide. The coating film protects the vapor-phase deposition film, thereby enhancing the gas barrier properties of the gas barrier layer.
[0046] The coating film is formed, for example, from a water-soluble polymer and an inorganic compound. The water-soluble polymer contains a hydroxyl group. The water-soluble polymer may be, for example, polyvinyl alcohol, polyvinylpyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, or the like. From the viewpoint of enhancing the gas barrier properties of the gas barrier layer 11, it is preferable that the water-soluble polymer is polyvinyl alcohol (PVA).
[0047] The inorganic compound contained in the coating film is, for example, Si(OR 1 )4 or R 2 Si(OR 3 In addition, the silicon compound may be a silicon compound represented by the formula OR 1 and OR 3 is a hydrolyzable group, R 2 is an organic functional group. The inorganic compound may include one or more silicon compounds or hydrolysates of such silicon compounds.
[0048] Si(OR 1 For example, R may be tetraethoxysilane (Si(OC2H5)4) (TEOS). TEOS is preferred because it is relatively stable in aqueous solvents after hydrolysis. 2 Si(OR 3 )3 contains R 2 is preferably selected from the group consisting of vinyl groups, epoxy groups, methacryloxy groups, ureido groups, and isocyanate groups.
[0049] The coating film is formed by applying a mixed solution of a solvent, a water-soluble polymer, and a silicon compound or a hydrolyzate of a silicon compound onto a deposition layer, followed by heating and drying. The solvent may be water or a mixed solvent of water and alcohol. When forming the mixed solution, first, the water-soluble polymer is dissolved in a solvent, and then the silicon compound or a hydrolyzate of a silicon compound is mixed. The mixed solution may contain additives to the extent that the coating film formed using the mixed solution does not lose its gas barrier properties. The additives may be, for example, an isocyanate compound, a silane coupling agent, a dispersant, a stabilizer, a viscosity modifier, and a colorant.
[0050] When the water-soluble polymer is PVA, the ratio of the mass of PVA to the mass of the total solid content of the mixed solution is preferably 20% by mass or more and 50% by mass or less, and more preferably 25% by mass or more and 40% by mass or less. By including 20% by mass or more of PVA, the flexibility of the coating film is maintained. Therefore, the coating film is easily formed. Furthermore, by including 50% by mass or less of PVA, the gas barrier layer 11 can have sufficient barrier properties.
[0051] The thickness of the coating film is selected, for example, from the range of 0.05 μm to 30 μm. When the gas barrier layer 11 includes a vapor-phase deposited film and a coating film, the vapor-phase deposited film is located on the resin film 10, and the coating film is located on the vapor-phase deposited film in the laminate 20. This allows the coating film to be in contact with the vapor-phase deposited film.
[0052] From the viewpoint of strengthening the adhesion between the resin film 10 and the gas barrier layer 11, a surface treatment such as a plasma treatment or a corona treatment may be performed on the surface of the resin film 10 on which the gas barrier layer 11 is formed. The plasma treatment may be, for example, a reactive ion etching (RIE) treatment, an inductively coupled plasma (ICP) etching, an ICP-RIE treatment, an atmospheric pressure plasma treatment, a flame treatment, or the like.
[0053] When the RIE treatment is performed on the first surface of the resin film 10, a modified layer is formed on the resin film 10. The modified layer includes the first surface of the resin film 10 before the RIE treatment is performed. The modified layer is a portion of the resin film 10 that has been modified by the RIE treatment on the first surface. The modified layer has a layer shape that includes the entire first surface.
[0054] According to the RIE treatment, for example, functional groups are imparted to the first surface of the resin film 10 by radicals and ions contained in the plasma. Also, for example, according to the RIE treatment, impurities attached to the first surface are removed by etching the first surface, and the surface roughness of the first surface is increased. That is, the modified layer is a layer in which functional groups are imparted to the PET forming the resin film 10, and the first surface is a layer in which the surface is cleaned and roughened. Therefore, the modified layer enhances the adhesion between the resin film 10 and the gas barrier layer 11. As a result, even in a high-temperature and high-humidity environment, peeling between the resin film 10 and the gas barrier layer 11 is unlikely to occur. That is, since the heat resistance of the laminate 20 is enhanced, when the laminate 20 is subjected to a heat treatment, peeling between the resin film 10 and the gas barrier layer 11 and deterioration of the gas barrier property of the gas barrier layer 11 are suppressed. The heat treatment is, for example, a boiling treatment, a retort treatment, and cooking.
[0055] The gas for generating plasma in the RIE process may be, for example, at least one of argon gas, oxygen gas, nitrogen gas, and hydrogen gas. When the gas barrier layer 11 is formed from an inorganic oxide, an anchor coat layer may be located between the resin film 10 and the gas barrier layer 11. The surface treatment and the anchor coat layer improve the adhesion between the resin film 10 and the deposition layer after heat sterilization, and the barrier properties of the laminate 20.
[0056] In addition to the above-mentioned vapor-deposited film and coating film, or instead of at least one of the above-mentioned vapor-deposited film and coating film, the gas barrier layer 11 may include a metal foil and a layer formed from a metal nitride. When the gas barrier layer 11 includes one or more layers other than the vapor-deposited film and coating film, another layer may be located between the vapor-deposited film and the coating film. Alternatively, another layer other than the coating film may be located between the vapor-deposited film and the resin film.
[0057] The laminate 20 may include a sealing layer, an adhesive layer, a decorative layer, and an information display layer in addition to the resin film 10 and the gas barrier layer 11. The sealing layer contains a thermoplastic resin. The sealing layer is melted by heat sealing when a package is formed using the laminate 20. As a result, in two laminates 20, an end of one laminate 20 is fused to an end of the other laminate 20. Alternatively, in one laminate 20, a first portion and a second portion of the laminate 20 are fused. The adhesive layer enhances adhesion between the gas barrier layer 11 and the upper layer of the gas barrier layer 11, or between the gas barrier layer 11 and the lower layer of the gas barrier layer 11. The decorative layer displays decoration and information formed by printing.
[0058] The thickness of the laminate 20 may be selected according to various resistances required for a package formed using the laminate 20 and the processability required for the laminate 20. The thickness of the laminate 20 may be, for example, 30 μm or more and 300 μm or less.
[0059] The laminate 20 may be formed by the above-mentioned film forming method, various coating methods, a dry lamination method, an extrusion lamination method, or the like.
[0060] [Packaging] The package will now be described with reference to FIG. The packaging body 30 shown in FIG. 3 is formed from a laminate 20. The packaging body 30 defines a space capable of accommodating a packaged object inside the packaging body 30. In the example shown in FIG. 3, the packaging body 30 has a bag shape. The packaging body 30 is sealed by joining the ends over the entire circumference. In the packaging body 30, the gas barrier layer 11 is located on the inner side relative to the resin film 10. The shape and size of the packaging body 30 are not particularly limited. The shape and size of the packaging body 30 may be designed according to the shape and size of the packaged object. The packaged object may be, for example, food, medicine, cosmetics, etc.
[0061] The method of joining the ends of the laminate 20 is not particularly limited. For example, the ends of the laminate 20 may be joined using heat sealing as described above, or may be joined by other methods. In the example shown in Fig. 3, the packaging body 30 has a sealing portion 31 in which the ends of the first laminate and the second laminate, which are two sheets of the laminate 20, are joined to each other.
[0062] The packaging body 30 is not limited to the bag-like shape shown in FIG. 3, but may have, for example, a cylindrical shape or a bag-like shape with one cylindrical end sealed and the other cylindrical end open.
[0063] [Example] Examples and comparative examples will be described with reference to FIG. 4 and Tables 1 and 2. [Example 1] Three resin layers were laminated by co-extrusion to form a resin film of Example 1 having a thickness of 12 μm. Each resin layer was formed from a mixture of recycled PET and virgin PET regenerated by mechanical recycling. In the entire resin film, the proportion of recycled PET was set to 80% by weight of the resin film, and the proportion of virgin PET was set to 20% by weight of the resin film. A part of the resin film was cut to prepare a measurement sample.
[0064] The surfaces of the measurement samples were analyzed by TOF-SIMS using a time-of-flight secondary ion mass spectrometer (ULVAC-PHI, Inc., TRIFT-V) under the following analytical conditions:
[0065] [Analysis conditions] Primary ion species Bi 3++ Acceleration voltage: 30kV ·Current 0.5μA Measurement time: 2 minutes -Static neutralization Yes Mass range: 1.5-5000emu Acquired ions: positive ions
[0066] [Etching conditions] Acceleration voltage: 20kV 5nA Sputtering time: 20sec
[0067] The C7H4O obtained by TOF-SIMS analysis for each resin film + The peak intensity of (m / z=104) is C3H5 + The normalized value divided by the peak intensity (m / z=41) was 0.3.
[0068] A part of this resin film was cut to form a cut piece, which was then dissolved in fluoroacetic acid as a solvent to prepare a sample for NMR measurement. Using a nuclear magnetic resonance device (AVANCE NEO400, manufactured by Bruker Japan), 1 The H-NMR spectrum was obtained. The measurement was performed with an accumulation time of 256 scans, a flip angle of 30°, a capture time of 4.19 sec, and a waiting time of 2.00 sec. 1 Using the H-NMR spectrum, the sum of the integrals of the signals of the terephthalic acid component, isophthalic acid component, naphthalenedicarboxylic acid component, ethylene glycol component, and diethylene glycol component, I sm Calculate the total I smwas set to "100 mol%". In addition, the integral value (I A ) and the integral value I of the signal of the naphthalenedicarboxylic acid unit at 8.34 ppm to 8.36 ppm B And the total I sm , the integral value I of the signal of isophthalic acid unit A , the integral value I of the signal of the naphthalenedicarboxylic acid unit B Using the above, the molar ratio of isophthalic acid units [(I A / I sm ) × 100%] and the molar ratio of naphthalenedicarboxylic acid units [(I B / I sm ) × 100% was calculated. The mole ratio of isophthalic acid units is 9 x 10 -1 mol%, and the molar ratio of naphthalenedicarboxylic acid units is 4×10 -2 It was mol%.
[0069] A vapor deposition film was formed on the resin film. A vacuum deposition apparatus using an electron beam heating method was used to form the vapor deposition film. Aluminum was evaporated while oxygen gas was introduced into a treatment chamber of the vacuum deposition apparatus, thereby forming an aluminum oxide film having a thickness of 15 nm.
[0070] A coating film was formed on the aluminum oxide film. When forming the coating film, a first liquid and a second liquid were prepared, and the solid content weight ratio (weight %) of the first liquid to the second liquid was set as follows: (Solid content weight ratio) 1st liquid: 2nd liquid = 70:30
[0071] In addition, 72.1 g of 0.1N hydrochloric acid was added to 17.9 g of tetraethoxysilane and 10 g of methanol, and the mixture was stirred for 30 minutes to hydrolyze tetraethoxysilane to prepare the first liquid. The solid content of the first liquid was 5 mass% in terms of SiO2. In addition, polyvinyl alcohol was dissolved in a solution of 95 mass parts of water and 5 mass parts of ethanol to prepare a second liquid. The solution of the first liquid and the second liquid was applied on the gas phase deposition film using a gravure coating method, and the solution was dried to form a coating film. As a result, the laminate for packaging of Example 1 was obtained.
[0072] [Example 2] The molar ratio of isophthalic acid units contained in the resin film is 9×10 -1 mol%, and the molar ratio of naphthalenedicarboxylic acid units is 6×10 -2 A laminate for packaging was produced in the same manner as in Example 1, except that the content was mol % and the standard value was 0.2.
[0073] [Example 3] The molar ratio of isophthalic acid units contained in the resin film is 7×10 -1 mol%, and the molar ratio of naphthalenedicarboxylic acid units is 6×10 -2 A laminate for packaging and a package were obtained in the same manner as in Example 1, except that the content was mol % and the standard value was 0.2.
[0074] [Example 4] The molar ratio of isophthalic acid contained in the resin film is 5×10 -1 mol%, and the molar ratio of naphthalene-2,6-dicarboxylic acid is 4 × 10 -2 Except for the fact that the content of the polyaniline in the resin film of Example 1 was 0.4, a laminate for packaging and a packaging body were obtained in the same manner as in Example 1. The spectrum shown in FIG. 4 was obtained by TOF-SIMS for the resin film of Example 1.
[0075] [Comparative Example 1] A PET film (Lumirror P60, manufactured by Toray Industries, Inc.) not containing a repeating unit derived from isophthalic acid and a repeating unit derived from naphthalenedicarboxylic acid and having a thickness of 12 μm was prepared as a resin film. In the resin film, signals at 7.11 ppm to 7.25 ppm and signals at 8.34 to 8.36 ppm were not detected. The standard value was 0.7. A laminate for packaging was produced in the same manner as in Example 1 except for the above.
[0076] [Evaluation method] [Face orientation coefficient] The plane orientation coefficient of the resin film was measured by a phase difference measurement method using a phase difference measurement device (KOBRA-WR, manufactured by Oji Scientific Instruments Co., Ltd.). Square measurement areas with a side length of 40 mm were set in the center row in the TD direction of the resin film and in the end row in the TD direction. In the measurement area, the phase difference was measured at incident angles of 0° to 50° (10° pitch).
[0077] [Gelboflex test] A Gelbo Flex test was performed on the test pieces made from the laminates of each of the Examples and Comparative Examples using a flexibility evaluation device (Gelbo Flex Tester, manufactured by Tester Sangyo Co., Ltd.). At this time, each test piece was attached to the fixed head of the flexibility evaluation device so as to have a cylindrical shape. In detail, both ends of each test piece were held by the fixed head, and the initial gripping distance was set to 175 mm. Then, the stroke was set to 87.5 mm, the twist was set to 440°, and the reciprocating motion of twisting and releasing each test piece was performed 100 times at a speed of 40 times / min.
[0078] [Oxygen permeability] The oxygen permeability of each test piece was measured before and after the Gelbo Flex test using an oxygen permeability measuring device (OX-TRAN 2 / 20, manufactured by Mocon). The method used was in accordance with JIS K 7126-2:2006 and ASTM D3985-81. The temperature was set to 30°C and the relative humidity was set to 70%. The unit of the measured oxygen permeability is [cm 3 (STP) / m 2 ·day·atm.
[0079] [Water vapor permeability] The water vapor permeability of each test piece was measured before and after the Gelbo Flex test using a water vapor permeability measuring device (Mocon, PERMATRAN-W 3 / 31). The measurements were performed at a temperature of 40°C and a relative humidity of 90%. The measurement method used was in accordance with JIS K 7129-2:2019 and ASTM F1249-90. The unit of the measured water vapor permeability is [g(STP) / m 2 -day] was set.
[0080] [Evaluation Results] The results of the measurements of the plane orientation coefficient, oxygen permeability, and water vapor permeability are shown in Table 1 below.
[0081] [Table 1]
[0082] As shown in Table 1, the oxygen permeability after the Gelbo Flex test in each Example was found to be smaller than the oxygen permeability after the Gelbo Flex test in Comparative Example 1. Also, the water vapor permeability after the Gelbo Flex test in each Example was found to be smaller than the water vapor permeability after the Gelbo Flex test in Comparative Example 1. Note that, before the Gelbo Flex test, the oxygen permeability of each Example and Comparative Example was found to be equivalent. Also, before the Gelbo Flex test, the water vapor permeability of each Example and Comparative Example was found to be equivalent.
[0083] [Example 5] The same resin film as in Example 1 was prepared, and one side of the resin film was subjected to RIE treatment using a hollow anode type plasma treatment device. In the RIE treatment, the applied power was set to 120 W, the treatment time was set to 0.1 sec, the treatment gas was set to argon, and the treatment unit pressure was set to 2.0 Pa. In addition, a high frequency power source having a frequency of 13.56 MHz was used.
[0084] A vapor deposition film was formed on the RIE-treated surface of the resin film. A vacuum deposition device using an electron beam heating method was used to form the vapor deposition film. Aluminum was evaporated while oxygen gas was introduced into the treatment chamber of the vacuum deposition device, forming an aluminum oxide film with a thickness of 15 nm.
[0085] A coating film was formed on the vapor deposition film. A mixed liquid of the first, second, and third liquids shown below was applied onto the vapor deposition film by gravure coating and dried to obtain a coating film. The thickness of the coating film was 0.3 μm.
[0086] First liquid: 17.9 g of tetraethoxysilane, 10 g of methanol, and 72.1 g of 0.1 N hydrochloric acid were mixed and stirred for 30 minutes to hydrolyze the tetraethoxysilane. This resulted in a hydrolysis solution with a solid content of 5 mass% calculated as SiO2.
[0087] Second liquid: Polyvinyl alcohol was dissolved to a concentration of 5% by mass in a solution obtained by mixing 5 parts by mass of ethanol with 95 parts by mass of water.
[0088] Third liquid: 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate, which is a silane coupling agent, was diluted with a mixed liquid obtained by mixing equal amounts of water and isopropyl alcohol in a mass ratio so that the solid content was 5 mass %.
[0089] The solid content weight ratios (% by weight) of the first liquid, the second liquid, and the third liquid were set as follows, and the blending ratio of the first liquid to the second liquid was set as follows. (Solid content weight ratio) 1st liquid: 2nd liquid: 3rd liquid = 70:20:10 (Mixing ratio) 1st liquid: 2nd liquid = 70:30 This resulted in a laminate for packaging comprising a gas barrier layer formed from the vapor deposition layer and the coating film, and a resin film.
[0090] Further, a 3 μm thick adhesive layer was formed on the coating film using a polyurethane adhesive. Next, a 70 μm thick non-oriented polypropylene film was laminated on the adhesive layer, and the non-oriented polypropylene film was laminated to the package laminate using the adhesive layer. A rectangular laminate piece having a short side with a length of 210 mm and a long side with a length of 297 mm was cut out from the laminate. The laminate piece was folded in half at the center of the long side so that a part of the gas barrier layer and the other part faced each other, and then the long side was heat-sealed to produce a package having an opening. For heat sealing, a tabletop degassing sealer (Fuji Impulse Co., Ltd., V-301) was used, and heat sealing was performed under conditions of 190° C., 0.3 MPa, and 2 sec. 150 mL of a 0.6% by mass aqueous cysteine solution was placed in the package, and the opening of the package was heat-sealed. This resulted in a sealed package.
[0091] In Example 5, a package was produced using a central row including the center in the TD direction of the original resin film, and a package was produced using an end row including one end in the TD direction. The molar ratios and standard values described above are values for the central row.
[0092] [Example 6] A laminate for packaging and a package were produced in the same manner as in Example 5, except that the same resin film as in Example 2 was prepared.
[0093] [Example 7] A laminate for packaging and a package were obtained in the same manner as in Example 5, except that the same resin film as in Example 3 was prepared.
[0094] [Example 8] A laminate for packaging and a package were obtained in the same manner as in Example 5, except that the same resin film as in Example 4 was prepared.
[0095] [Comparative Example 2] A laminate for packaging and a package were produced in the same manner as in Example 5, except that the same resin film as in Comparative Example 1 was prepared.
[0096] [Evaluation method] [Face orientation coefficient] The plane orientation coefficient of the resin film was measured by a phase difference measurement method using a phase difference measurement device (KOBRA-WR, manufactured by Oji Scientific Instruments Co., Ltd.). Square measurement areas with a side length of 40 mm were set in the center row in the TD direction of the resin film and in the end row in the TD direction. In the measurement area, the phase difference was measured at incident angles of 0° to 50° (10° pitch).
[0097] [Retort processing] Two packages were prepared for each of the examples and the comparative examples. Then, using a hot water storage retort cooker, one package was heated at 110°C for 110 minutes (heating condition 1), and the other package was heated at 130°C for 30 minutes (heating condition 2). For test pieces made from each package, the oxygen transmission rate, water vapor transmission rate, and laminate strength were measured under the conditions described below.
[0098] [Oxygen permeability] The oxygen permeability of each test piece was measured using an oxygen permeability measuring device (OX-TRAN 2 / 20, manufactured by Mocon). The method used was in accordance with JIS K 7126-2:2006 and ASTM D3985-81. The temperature was set to 30°C and the relative humidity was set to 70%. The unit of the measured oxygen permeability is [cm 3 (STP) / m 2·day·atm.
[0099] [Water vapor permeability] The water vapor permeability of each test piece was measured using a water vapor permeability measuring device (PERMATRAN-W 3 / 31, manufactured by Mocon). The measurements were performed under conditions of a temperature of 40°C and a relative humidity of 90%. The measurement method used was in accordance with JIS K 7129-2:2019 and ASTM F1249-90. The unit of the measured water vapor permeability is [g(STP) / m 2 -day] was set.
[0100] [Laminate strength (dry condition)] A rectangular test piece with a short side length of 15 mm and a long side length of 200 mm was cut out from the package after retort treatment. Using a Tensilon universal material testing machine (Tensilon UMT-II-500, manufactured by Toyo Baldwin Co., Ltd.), the temperature was set to 23°C and the relative humidity was set to 65%, and the laminate strength (N / 15 mm) was measured. The tensile speed was set to 200 mm / min, and the peel angle was set to 90°.
[0101] [Laminate strength (wet conditions)] From the package after retort treatment, the same test pieces as those for measuring the laminate strength under dry conditions were cut out. The test pieces were subjected to a moist heat treatment by holding them in hot water at 130°C for 30 minutes. The laminate strength (N / 15mm) of the undried test pieces was measured using a Tensilon universal material testing machine (Tensilon UMT-II-500, manufactured by Toyo Baldwin Co., Ltd.) at a temperature of 23°C and a relative humidity of 65%. The laminate strength was measured at a tensile speed of 200mm / min and a peel angle of 90°.
[0102] [Evaluation Results] The measurement results of the plane orientation coefficient, oxygen permeability, water vapor permeability, and laminate strength are shown in Table 2 below.
[0103] [Table 2]
[0104] As shown in Table 2, regardless of the heating conditions during retort and the position on the original roll of the resin film, the oxygen permeability of each Example was found to be smaller than the oxygen permeability of Comparative Example 2. In addition, regardless of the heating conditions during retort and the position on the original roll of the resin film, the water vapor permeability of each Example was also found to be smaller than the water vapor permeability.
[0105] Thus, it was found that the laminate for packaging of each Example had improved airtightness after retort treatment. As shown in Table 2, when retort treatment was performed under heating condition 1, it was confirmed that the laminate strength under dry conditions in each Example was higher than the laminate strength under dry conditions in Comparative Example 2. In addition, when retort treatment was performed under heating condition 1, it was confirmed that the laminate strength under wet conditions in each Example was equivalent to the laminate strength under wet conditions in Comparative Example 2.
[0106] When retort treatment was performed under heating condition 2, it was confirmed that the laminate strength under dry conditions in each Example was equivalent to that of Comparative Example 2. In addition, when retort treatment was performed under heating condition 2, it was confirmed that the laminate strength under wet conditions in each Example was equivalent to that of Comparative Example 2.
[0107] Thus, it was found that the laminate for packaging of each Example had improved airtightness of the package compared to the laminate for packaging of the Comparative Example. As described above, according to one embodiment of the resin film for packaging, the laminate for packaging, and the packaging body, the following effects can be obtained.
[0108] (1) It is possible to improve the airtightness of the packaging body 30 including the resin film 10. (2) The laminate 20 including the resin film 10 and the gas barrier layer 11 prevents deterioration in the gas barrier properties of the laminate 20. This enhances the suitability of the laminate 20 for use as a packaging material.
[0109] (3) The packaging body 30 formed from the laminate 20 prevents deterioration of the gas barrier properties of the packaging body 30 due to vibrations or the like applied to the packaging body 30 during transportation of the product. This prevents deterioration in the quality of the object packaged in the packaging body 30. [Explanation of symbols]
[0110] 10...Resin film 11...Gas barrier layer 20...Laminate 30...Packaging body
Claims
1. A resin film for packaging used to form a gas barrier layer, Contains polyethylene terephthalate, The polyethylene terephthalate includes recycled polyethylene terephthalate which is at least one of polyethylene terephthalate regenerated by mechanical recycling and polyethylene terephthalate regenerated by chemical recycling; When analyzed using time-of-flight secondary ion mass spectrometry (TOF-SIMS), 7 H 4 O + (m / z = 104) peak intensity is C 3 H 5 + The normalized value divided by the peak intensity of (m / z=41) is within the range of 0.1 to 0.
5. Resin film for packaging.
2. The proportion of repeating units derived from isophthalic acid in all dicarboxylic acid units of the polyethylene terephthalate is 0.5 mol % or more and 5 mol % or less. The resin film for packaging according to claim 1.
3. The polyethylene terephthalate contains, as polyester dicarboxylic acid units, a terephthalic acid component, an isophthalic acid component, and a naphthalenedicarboxylic acid component, When the total amount of the terephthalic acid component, the isophthalic acid component, the naphthalenedicarboxylic acid component, the ethylene glycol component and the diethylene glycol component contained as diol units is taken as 100 mol %, the molar ratio of the isophthalic acid component to the total amount is 2×10 -1 mol% or more 9×10 -1 mol % or less, and the molar ratio of the naphthalenedicarboxylic acid component is 1×10 -2 mol% or more 6×10 -2 mol% or less The resin film for packaging according to claim 1.
4. the surface on which the gas barrier layer is to be formed has been subjected to a plasma treatment or a corona treatment; The plasma treatment is any one of reactive ion etching, inductively coupled plasma etching, ICP-RIE treatment, atmospheric pressure plasma treatment, and flame treatment. The resin film for packaging according to claim 1.
5. The formation of the gas barrier layer is the formation of an inorganic oxide film or a metal film by any one of a vacuum deposition method, a sputtering method, an ion plating method, and a plasma vapor phase epitaxy method. The resin film for packaging according to claim 1.
Citation Information
Patent Citations
Method for recycling pet bottle
JP2002161166A
Laminated film
JP2017210002A
Film deposition apparatus of vapor-deposited film, and film deposition method of vapor-deposited film
JP2019123925A
Barrier film and packaging material
JP2020029095A
Gas barrier vapor deposition film, gas barrier laminate, gas barrier packaging material, gas barrier packaging material, and method for producing gas barrier vapor deposition film
JP2020100040A